2005
DOI: 10.1007/s10038-005-0329-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a methylenetetrahydrofolate-dehydrogenase 1958G>A polymorphism for neural tube defect risk

Abstract: Genetic variants of enzymes involved in the folate pathway might be expected to have an impact on neural tube defect (NTD) risk. Given its key role in folate metabolism, the methylenetetrahydrofolate dehydrogenase 1 (MTHFD1) gene could represent an attractive candidate in NTD aetiology. In this study, the impact of the MTHFD1 1958G>A polymorphism on NTD risk in the Italian population was examined both by hospital-based case-control and family-based studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 21 publications
(20 reference statements)
3
47
0
2
Order By: Relevance
“…Low 1958AA homozygous genotype frequency (5.4% in controls) was also reported in Chinese population by Wang et al (2007a). MTHFD G1958A polymorphism may result in disturbance of the folate-mediated Hcy pathway and has been observed with increased risk of birth defects such as NTD and unexplained second semester pregnancy loss (Parle-McDermott et al, 2005;De Marco et al, 2006). However, in the present study, this mutant was not associated with an increased risk for giving birth to a DS child.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Low 1958AA homozygous genotype frequency (5.4% in controls) was also reported in Chinese population by Wang et al (2007a). MTHFD G1958A polymorphism may result in disturbance of the folate-mediated Hcy pathway and has been observed with increased risk of birth defects such as NTD and unexplained second semester pregnancy loss (Parle-McDermott et al, 2005;De Marco et al, 2006). However, in the present study, this mutant was not associated with an increased risk for giving birth to a DS child.…”
Section: Discussionsupporting
confidence: 51%
“…The MTHFD G1958A polymorphism reduces the enzyme's activity and stability, and has been associated with an increased risk of NTD (De Marco et al, 2006). Transcobalamin (TC), a cobalamin-transporting protein, plays an important role in vitamin B12 cellular uptake and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that MTHFD1-G1958A could be a maternal NTD risk factor [28,29], but not a children factor. However, De Marco et al [30] found an increased risk for heterozygous 1958G/A and homozygous 1958A/A genotypes in children. Our results also indicated a negative association between MTHFD1-G1958A and NTDs, consistent with conclusions from studies by Parle-McDermott and Brody.…”
Section: Discussionmentioning
confidence: 99%
“…Family-based tests also confirmed a significant excess of transmission of the 1958A allele to affected individuals, demonstrating that this variant is a genetic risk factor for Italian NTD cases. [44] A potential role of the mitochondrial paralogue MTHFD1L as candidate gene for NTDs association has been also investigated. In particular, a common triallelic deletion/insertion variant 781-6823ATT(7-9) which influences splicing efficiency was tested and a significant incresead risk for allele 1 [ATT (7)] was identified.…”
Section: Variantmentioning
confidence: 99%